Thyroid Disruptors: How They Act and How We React - Bufalo, Natassia Elena; Silva, Aline Carolina de Nadai da; Barbieri, Raquel Bueno; Marcello, Marjory Alana; Cunha, Lucas Leite; Morari, Elaine Cristina; Ward, Laura Sterian (IntechOpen, 2011)
None